A Robust Chaos-Based True Random Number Generator Embedded in Reconfigurable Switched-Capacitor Hardware - Drutarovsky, Milos; Galajda, Pavol (Společnost pro radioelektronické inženýrství, 2007)
This paper presents a new chaos-based True Random Number Generator (TRNG) with a decreased voltage supply sensitivity. Contrary to the traditionally used sources of randomness it uses a well-defined deterministic switched-capacitor circuit that exhibits chaos. The whole design is embedded into a commercially available mixed-signal Cypress PSoC reconfigurable device without any external components. The proposed design is optimized for a reduction of influence of the supply voltage to the quality of the generated random bit stream. The influence of circuit non-idealities is significantly reduced by the proposed XOR corrector and optimized circuit topology. The ultimate output bit rate of the proposed TRNG is 60 kbit/s and the quality of generated bit-streams is confirmed by passing standard FIPS and correlation statistical tests performed in the full range of PSoC device supply voltages.
Keywords: Cryptography; chaos; Markov chains; TRNG; PSoC mixed-signal hardware; FIPS tests